The Merger of Indonesian Islamic Banks: Impact on the Islamic Economy Development - Ghozali, Mohammad; Kamri, Norazzah Binti; Khafid, M. Ali Zi (AL- IKTISAB Journal of Islamic Economic Law, 2022)
••• English ••• The development of Islamic banking and financial institutions in Indonesia is getting better from year to year. This development is a benchmark for the success of the Islamic economy. To become a new economic force in Indonesia, the Minister of State Owned Enterprises stated that there are plans to merge state owned Islamic banks namely BRI Syariah, BNI Syariah, and Bank Syariah Mandiri, as the total assets of Islamic banks will increase and become larger in Indonesia. This research aims to determine the impact of the merger of three Indonesian Islamic banks in the development of the Islamic economy. The research employed a qualitative method with a library research approach. The results have shown that the merger of three Islamic banks consisting of Bank BRI Syariah, Bank BNI Syariah, and Bank Syariah Mandiri into Bank Syariah Indonesia (BSI) has positive impacts on the Islamic economy development in Indonesia. Firstly, the increase in banking capital as a result of the merger of the three banks, the increase in economic activity in the field of Islamic capital markets, the promotion of the halal system in all service activities in banking. Secondly, the merger still allows customers to transact using their old accounts from their respective banks throughout the transaction period starting from e-Money, Tapcash, Brizzi, and or card based electronic money. Thirdly, all employees of the three banks are still employees of BSI and there are no layoffs despite the merger of three Islamic banks, and BSI opens talent development programs to all Indonesians to prepare Islamic bank leaders in the future. Fourthly, BSI created a talent development program for the Indonesian community to increase literacy and understanding of Islamic economics and work with economists and Islamic institutions to support the program, promote Islamic economic development by accelerating the completion of the halal value chain. ••• Indonesian ••• Perkembangan perbankan dan lembaga keuangan syariah di Indonesia semakin baik dari tahun ke tahun. Perkembangan ini menjadi tolak ukur keberhasilan ekonomi syariah. Untuk menjadi kekuatan ekonomi baru di Indonesia, Menteri Badan Usaha Milik Negara menyatakan rencana untuk menggabungkan bank syariah milik negara yaitu BRI Syariah, BNI Syariah, dan Bank Syariah Mandiri, karena total aset bank syariah akan meningkat dan menjadi lebih besar di Indonesia. Penelitian ini bertujuan untuk mengetahui dampak merger tiga bank syariah Indonesia terhadap perkembangan ekonomi syariah. Penelitian ini menggunakan metode kualitatif dengan pendekatan penelitian kepustakaan. Hasil penelitian menunjukkan bahwa penggabungan tiga bank syariah yang terdiri dari Bank BRI Syariah, Bank BNI Syariah, dan Bank Syariah Mandiri ke dalam Bank Syariah Indonesia (BSI) berdampak positif bagi perkembangan ekonomi syariah di Indonesia. Pertama, peningkatan permodalan perbankan akibat penggabungan ketiga bank tersebut, peningkatan kegiatan ekonomi di bidang pasar modal syariah, promosi sistem halal dalam semua kegiatan pelayanan di perbankan. Kedua, penggabungan masih memungkinkan nasabah untuk bertransaksi menggunakan rekening lama dari bank masing-masing selama periode transaksi mulai dari e-Money, Tapcash, Brizzi, dan atau uang elektronik berbasis kartu. Ketiga, seluruh pegawai ketiga bank tersebut masih pegawai BSI dan tidak ada PHK meskipun tiga bank syariah telah bergabung, dan BSI membuka program pengembangan talenta kepada seluruh masyarakat Indonesia untuk mempersiapkan pemimpin bank syariah di masa depan. Keempat, BSI membuat program pengembangan talenta bagi masyarakat Indonesia untuk meningkatkan literasi dan pemahaman ekonomi syariah serta bekerjasama dengan para ekonom dan lembaga syariah untuk mendukung program tersebut, mendorong pengembangan ekonomi syariah dengan mempercepat penyelesaian rantai nilai halal.